A Process Model for the Implementation of Blockchain-Based Systems - Muhammad Nasim Bahar; Michal Ries; Kristian Kostal (IEEE Access)
Although blockchain technology has immense potential to revolutionize various industries, its practical adoption faces significant challenges. This study tackles these hurdles by introducing a process model for the implementation of a blockchain-based system (PM-IBS), a comprehensive framework that guides organizations through the complexities of the adoption of blockchain systems. The model offers a structured approach that includes decision trees for suitability evaluation, platform selection guidance, high-level architectural design strategies, cost estimation techniques, and an understanding of best practices and design principles. Furthermore, a real-world use case, “Blockchain-Based Property Registration and Succession System,” exemplifies the model’s applicability in tackling practical challenges. Finally, a comprehensive feedback survey evaluated the PM-IBS model in various dimensions, providing valuable information on its strengths and potential improvements. This dual contribution of a novel process model, functional prototype, real-world use case, and user feedback significantly enriches the knowledge of blockchain adoption strategies. The PM-IBS model empowers organizations to overcome adoption barriers and leverage the transformative power of blockchain technology.